Functional significance of stereopsis in professional table-tennis players - Zhu, X. J.; Li, Y. H.; Liu, L. Q. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Stereopsis is the most important part of depth perception, especially in athletic population. At present, there are few studies on how to comprehensively evaluate athletes` stereoscopic function and how the impairment of stereoscopic function affects sports performance. METHODS: Twenty-two professional table-tennis players from Sichuan Province Team were recruited as player group and 23 age-matched students were recruited as the controls. All subjects were measured the habitual visual acuity, best corrected visual acuity, dominant eye, retinoscopy and three stereo acuity tests. Both groups completed two motor skills tasks: Purdue Pegboard and beads threading with habitual binocular viewing and monocular viewing by covering dominant eye. In addition, the player group was asked to complete a brief questionnaire and catch balls served by the auto table-tennis machine under two viewing conditions. RESULTS: The player group had better stereo acuity with median values of 60, 25 and 40 arc sec in TNO, Butterfly, and Frisby tests, respectively. There had statistically correlations between stereo acuity and two motor skills tasks. Both the two tasks were statistically significant different between binocular and monocular viewings in both groups. The player group had better performance on Purdue Pegboard task with binocular viewing (16±1.1, P=0.006) compared to the control group, while no statistical difference was found under monocular condition in beads threading task. In player group, the brief questionnaire demonstrated very negative feeling of players under monocular viewing and the number of catching balls had statistically significant difference between binocular (9.9±0.3) and monocular (6.9±1.6) viewings (P<0.001). CONCLUSIONS: Stereopsis plays an important role in sports performance, the stereo tests combined with Purdue pegboard can be used to evaluate athletes` stereoscopic function comprehensively.